2007
DOI: 10.1007/s11663-006-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

Casting Simulation of Calcium Titanate and Calcium Zirconate Nozzles for Continuous Casting of Aluminum-Killed Steels

Abstract: The clogging of submerged entry nozzles (SENs) and tundish well nozzles is a common problem in the continuous casting of aluminum-killed steels. Clogging occurs when alumina attaches to the inside of the nozzle restricting the flow. This article explores the use of new nozzle materials that could prevent accretion growth through the formation of liquid phases at the inclusionrefractory interface. Casting simulation experiments were conducted using three nozzle refractory formulations: calcium titanate, calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 3 publications
2
27
0
Order By: Relevance
“…Furthermore, Ca containing nozzle materials, which can react with alumina and form liquid calcium aluminates, were found to partly prevent clogging. 18 Similar results have been found when trying to decrease clogging by controlling the oxygen potential, slag carryover and stirring practices. 19 Clogging of REM treated steels has also been studied.…”
Section: Introductionsupporting
confidence: 66%
“…Furthermore, Ca containing nozzle materials, which can react with alumina and form liquid calcium aluminates, were found to partly prevent clogging. 18 Similar results have been found when trying to decrease clogging by controlling the oxygen potential, slag carryover and stirring practices. 19 Clogging of REM treated steels has also been studied.…”
Section: Introductionsupporting
confidence: 66%
“…8 mm from the down end of the carbon bonded nozzle with the active alumina coating is presented. Two main clogging areas are identified, (a) a ''denser clogging area'' in the range of 35 mm, which is mostly fixed at the alumina active coating, and (b) a ''coral-like clogging area'' in the range of 50 mm as also described by Tuttle et al [10]. The ''denser clogging area'' consists of steel clogged small and bigger particles, especially the bigger ones in the range of 5-15 mm.…”
Section: Resultsmentioning
confidence: 67%
“…Rackers and Thomas present four general types of clogging, each from a different origin. [9] Tuttle et al [10] have studied clogging phenomena of refractory model nozzles based on carbon bonded alumina, calcium zirconate, calcium titanate and mixtures of the two oxide materials.…”
Section: Introductionmentioning
confidence: 99%
“…F) "Coral-like" zone consisting of endogenous alumina particles in complex shapes. [12] The clogging phenomenon of submerged nozzles represents one major problem in the continuous casting process of steel, because it degrades the quality of the products and reduces the productivity of the equipment. Poirier et al studied the deposits in the submerged nozzles and observed (as on the filters) a decarburized area followed by layers of alumina particles with a plate-like shape and size up to 20 mm.…”
Section: Introductionmentioning
confidence: 99%